2022
DOI: 10.1038/s41598-022-08936-0
|View full text |Cite
|
Sign up to set email alerts
|

PPP6C, a serine-threonine phosphatase, regulates melanocyte differentiation and contributes to melanoma tumorigenesis through modulation of MITF activity

Abstract: It is critical to understand the molecular mechanisms governing the regulation of MITF, a lineage specific transcription factor in melanocytes and an oncogene in melanoma. We identified PPP6C, a serine/threonine phosphatase, as a key regulator of MITF in melanoma. PPP6C is the only recurrently mutated serine/threonine phosphatase across all human cancers identified in sequencing studies and the recurrent R264C mutation occurs exclusively in melanoma. Using a zebrafish developmental model system, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Beyond that, IRF5 has been proven to improve PPP6C transcription through directly binding to the PPP6C promoter region, implying that PPP6C was a new IRF5‐target gene. As a serine–threonine phosphatase, PPP6C has been confirmed to promote the tumorigenesis and development of multiple human cancers 32–34 . Consistent with the former report, 27 we found that PPP6C content was clearly elevated in CC samples and cell lines.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Beyond that, IRF5 has been proven to improve PPP6C transcription through directly binding to the PPP6C promoter region, implying that PPP6C was a new IRF5‐target gene. As a serine–threonine phosphatase, PPP6C has been confirmed to promote the tumorigenesis and development of multiple human cancers 32–34 . Consistent with the former report, 27 we found that PPP6C content was clearly elevated in CC samples and cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…As a serine-threonine phosphatase, PPP6C has been confirmed to promote the tumorigenesis and development of multiple human cancers. [32][33][34] Consistent with the former report, 27 we found that PPP6C content was clearly elevated in CC samples and cell lines. Apart from that, IRF5 absence-mediated CC cell growth and glycolysis inhibition were partly overturned by PPP6C upregulation.…”
Section: Previous Reports Have Suggested the Oncogenic Function Of Irf5supporting
confidence: 90%
“…One of the most established factors that controls neural-crest migration, and melanocyte differentiation, is the expression level of microphthalmia-associated transcription factor ( MITF ). In melanoma cell biology, MITF is a central player, controlling aspects of phenotypic switching ( 68 ), and is one of several critical transcriptional regulators involved in melanocyte development, upregulating a set of genes to drive melanocytic differentiation ( 3 ). All melanomas exhibit at least two distinct MITF transcriptional cell states, which are represented by melanomas with high levels of MITF , versus melanomas with low levels of MITF ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of melanoma has increased continuously over the past 30 years ( 1 ) and cutaneous malignant melanoma accounts for 73% of skin cancer-related death ( 2 ). Although targeted therapies and immune checkpoint inhibitors (ICI) have become available to treat cutaneous melanoma ( 3 ), unfortunately, half of all the patients respond poorly to currently available targeted therapies and only 20–40% of melanoma patients respond well to anti-PD1 ICI monotherapies. Treatment with a combination of these drugs can result in approximately 60% response rates being achieved ( 4 ), but resistance to therapy and disease recurrence is very common, despite recent therapeutic advances provided by immunotherapy and targeted drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown the functional impact of PPP2R1A-179 in UCEC ( n = 26) [ 27 , 31 ] and CIC-215 in glioblastomas [ 32 ]. Other less frequent but known hotspots include VHL-158 in KIRC ( n = 7) [ 33 ], PPP6C-264 in SKCM ( n = 7) [ 34 ], and SF3B1-625 in UVM ( n = 13) [ 35 ]. The hotspot RUNX1-96 in BRCA, which is formed by frameshifts and lacks death events, has not been thoroughly studied.…”
Section: Resultsmentioning
confidence: 99%